Chemical Synthesis of the PAX Protein Inhibitor EG1 and Its Ability to Slow the Growth of Human Colorectal Carcinoma Cells - McDougall, Lorissa; Kueh, Jui Thiang Brian; Ward, Jake; Tyndall, Joel D. A.; Woolley, Adele G.; Mehta, Sunali; Stayner, Cherie; Larsen, David S.; Eccles, Michael R. (Frontiers in Oncology, 2021)
Colorectal cancer is primarily a disease of the developed world. The incidence rate has continued to increase over time, reflecting changes in both demographic and lifestyle, which has resulted in genomic and epigenomic modifications. Many of the epigenetic modifications occur in genes known to be closely associated with embryonic development and cellular growth. In particular, the paired box (PAX) transcription factors are crucial for correct tissue development during embryogenesis due to their role in regulating genes involved in proliferation and cellular maintenance. In a number of cancers, including colorectal cancer, the PAX transcription factors are aberrantly expressed, driving proliferation and thus increased tumour growth. Here we have synthesized and used a small molecule PAX inhibitor, EG1, to inhibit PAX transcription factors in HCT116 colorectal cell cultures which resulted in reduced proliferation after three days of treatment. These results highlight PAX transcription factors as playing an important role in the proliferation of HCT116 colorectal cancer cells, suggesting there may be a potential therapeutic role for inhibition of PAX transcription factors in limiting cancer cell growth.